A five consecutive years' study of renal function outcome among biopsy proven lupus nephritis patients in Southern Iran. (September 2017) - Pakfetrat, M; Malekmakan, L; Kamranpour, M; Tadayon, T
Introduction: Lupus nephritis (LN) is one of the most common complications of systemic lupus erythematous (SLE) responsible for an increase in mortality and morbidity. This study was conducted to evaluate the outcome for LN patients and factors that correlate with their outcome. Materials and methods: We included 80 patients with proved LN and more than three-years follow up at Shiraz University of Medical Sciences. We prepared a data gathering sheet for each patient and extracted the data from patients' file records which existed in the hospital. Results: The mean age of patients was 36.6 ± 10.6 years, and 88.3% of patients were women. Men develop remission less than women (three men (33.3%) vs 49 women (72.1%), p = 0.014). Chronic kidney disease (GFR < 60) developed in 14.2% of our patients, and 7.8% progressed to end stage renal disease (ESRD). We found a significant relation between initial creatinine (Cr), GFR, and urine 24 hour protein with developing ESRD ( p = 0.002, 0.039, < 0.001, respectively). Also we found that hypertensive patients are at risk of developing ESRD 0.4 times more than normotensive patients ( p = 0.047, CI: 0.131–0.985). Lack of remission was significantly associated with ESRD progression ( p = 0.025). Conclusion: There is a strong agreement among studies that initial Cr, hypertension and lack of remission are associated with poor outcome in LN patients. As a result we must observe hypertensive patients and patients with increased Cr more carefully. Also, we should consider changing treatment in patients who do not develop remission. In spite of dominancy of women in SLE, men are likely to have poorer outcomes.